Research of lightning protection method of direct distribution line of ventilator station of a coal mine - ZHOU Yilong; XIONG Jiawei; DENG Jiewen; ZHAO Xian; YANG Pinghua; TONG Nian (Gong-kuang zidonghua, 2014)
In view of problem that rotary motor of direct distribution line is easy to be damaged by lightning, the paper analyzed status of lightning protection of direct distribution line of ventilator station of a coal mine and its problems, indicated that the direct distribution line only depends on protection of arrester is inadequate, the lightning protection of the rotary motor should consider protection requirements of main insulation, turn-to-turn insulation and neutral-point insulation. It proposed a safe and reliable lightning protection method, namely the method parallels capacitor in arrester end of bus side and series reactance in incoming end of cable for the direct distribution line, and made effect analysis for the lightning protection method from main insulation, turn-to-turn insulation and prevention of lighting induced voltage of the rotary motor. The simulation result shows that the lightning protection method can effectively limit gradient and amplitude of incoming lightning.